Literature Review of Treasury Cash Flow Forecast - Hua, Shi (Advances in Social Sciences Research Journal, 2020)
In this paper, the related literatures of treasury cash flow forecasting in the early stage are reviewed. By reviewing the related literatures, it is found that the treasury cash flow forecasting in China has made great progress, and various forecasting methods have been used in practical work, but there is still room for optimization in treasury cash flow forecasting. Suggestions for optimization are put forward.